The Impact of Childhood Behavior Problems on Child Care and Employment Decision-Making: A Nationally Representative Panel Study - Montes, Guillermo ([Verlag nicht ermittelbar], 2013)
A nationally representative panel study of parents and children, the Impact of Childhood Behavior Problems on Child Care and Employment Decision-Making Study was designed to determine the type of employment problems that parents directly attribute to difficulties in securing child care by using a household approach and to identify whether having a child with behavior problems or chronic illness is independently associated with child care-related employment problems in the United States. The study included parents of children aged 0 to 13 years and employed household level sampling from a nationally representative random-digit dial Gallup panel. Post-stratification weighting was accomplished by applying weights based on census region, income, and education using Stata's post-stratification commands. Nine measures of child care-related employment problems were included in the telephone survey instrument and include: Child Care-Related Employment Problems - Child care was defined broadly, including standard child care arrangements, before and after school activities or programs, babysitters, etc. Regular child care arrangements were defined as a regularly attended program, activity, or arrangement that occurs at least once a week. There were nine measures of child care related employment problems. Respondents were asked, "As a result of problems with child care during this school year, has a parent in your household": (a) quit a job (b) been absent from work (c) decreased job performance (d) changed a work schedule (e) looked for a different job (f) modified current job substantially (g) turned down a job (h) stopped looking for work (i) made decisions that will negatively impact future employability Behavior Problems and Current Serious Health Condition - The presence of behavior problems was determined by combining questions dealing with (1) defiant, aggressive behavior or conduct and (2) behavior problems. Similarly, parents were asked if their child had a serious chronic health condition that warranted medical treatment in the last 12 months. Household Composition - Parents were asked whether they are part of a two-parent/single-parent household or a stay-at-home parent household. Demographic Variables - Respondent's gender and race were collected, as well as information about the highest level of education and annual income. Overall, almost half (46 percent) of households reported at least one child care-related employment change. The two most common changes cited were being absent from work (21 percent) and changing the work schedule (27 percent). Two-parent households were significantly less likely to report child care-related employment changes compared to single parent households. In addition, households with a stay-at-home parent were less likely to report child care-related absenteeism, but were more likely to report recently quitting a job than households without a stay-at-home parent. Also, having a child with behavior problems or a serious chronic health condition was associated with up to triple odds of many child care-related employment problems. These findings support the notion that child care-related employment problems are common among families with a child with chronic illness or behavior problems, and support the need for policy makers to strive for implementation of more parent-friendly working conditions.